The relationship between health literacy and stages of change in smoking behavior among employees of educational health centers of Tabriz University of Medical Sciences (2016) - Shirin Barzanjeh Atri (International Journal of Preventive Medicine, 2018)
Background: Health literacy has been considered as a predictor of starting, maintaining, and stop smoking. However, such relations have not been well documented in previous texts. Therefore, the purpose of this study was to investigate the relation between health literacy and changes in the behavior of smoking in Tabriz University of Medical Sciences. Methods: In this correlational descriptive study, a total of 297 employees of Tabriz health centers were examined. To collect data, a demographic-social questionnaire, Iranian Health Literacy Questionnaire, and DiClemente's behavior change questionnaire were used. Besides, SPSS 13 software (significance level = 0.05) was employed to analyze the data. Results: The average health literacy rate of participants was 70, and most respondents had adequate health literacy. Nearly 41.1% were in the precontemplation phase which is one of the stages of behavior change. There was a positive and significant statistical relation between behavior change variable with all health literacy areas (except the scope of understanding) and total health literacy score (P = 0.011 and r = 0.147). The results of ordinal regression analysis demonstrated that there is a significant positive relationship between the score of health literacy and behavioral change (b = 0.019, 95% confidence interval = (0.010–0.029), P < 0.001). Conclusions: Improving the level of health literacy can lead to change people's behavior in relation to tobacco consumption. However, due to the lack of relevant texts, there is a need for further studies in this field.